ChemInform Abstract: Cytotoxic ent‐Kaurane Diterpenoids from Isodon nervosus. Issue 1 (7th January 2014) - Gao, You‐Heng; Wei, Zhi‐Xiong; Cheng, Yi; Wang, Teng‐Hua; Ni, Lin; Zhou, Xiao‐Hong; Zhang, Li‐Yuan
Abstract The diterpenoids rabdonervosins G‐J [(I) ‐ (IV)] are isolated from the leaves and stems of title plant.